2006
DOI: 10.1128/aem.00137-06
|View full text |Cite
|
Sign up to set email alerts
|

A Virulence and Antimicrobial Resistance DNA Microarray Detects a High Frequency of Virulence Genes in Escherichia coli Isolates from Great Lakes Recreational Waters

Abstract: Escherichia coli is generally described as a commensal species with occasional pathogenic strains. Due to technological limitations, there is currently little information concerning the prevalence of pathogenic E. coli strains in the environment. For the first time, using a DNA microarray capable of detecting all currently described virulence genes and commonly found antimicrobial resistance genes, a survey of environmental E. coli isolates from recreational waters was carried out. A high proportion (29%) of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
96
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 38 publications
14
96
2
3
Order By: Relevance
“…coli pathotypes such as STEC, EPEC, ETEC, and ExPEC and their associated VGs were selected in this study, as other studies have reported the presence of these pathotypes, originating from sewage and/or animal feces, in environmental water (23,24,25,38,46). Overall, 30 (15%) of 200 isolates from eight tanks were positive for the eaeA gene, which belongs to STEC or EPEC (25).…”
Section: Discussionmentioning
confidence: 99%
“…coli pathotypes such as STEC, EPEC, ETEC, and ExPEC and their associated VGs were selected in this study, as other studies have reported the presence of these pathotypes, originating from sewage and/or animal feces, in environmental water (23,24,25,38,46). Overall, 30 (15%) of 200 isolates from eight tanks were positive for the eaeA gene, which belongs to STEC or EPEC (25).…”
Section: Discussionmentioning
confidence: 99%
“…Prehybridization and hybridizations were performed as previously described (19), with the following modifications: hybridizations were performed using a Slide Booster hybridization work station (model SB800; Advalytix, Germany), and scanning was performed using a ScanArray Lite fluorescent microarray analysis system (Perkin-Elmer, Mississauga, ON, Canada) with images scanned at 5-m resolution and laser power set to 95%. Acquisition of fluorescent spots and quantification of fluorescent spot intensities were performed as described by Hamelin et al (19).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, an E. coli DNA virulence microarray previously employed to assess the genotypes (virulence and antibiotic resistance genes) of E. coli strains isolated from different environmental ecosystems and from the chicken intestinal tract (1,10,19,20,33) was used. The aim of the present trial was to investigate the distributions of pathotypes and of virulence and antibiotic resistance genes in E. coli isolates from broilers fed with antimicrobial supplementation diets including bambermycin, penicillin, salinomycin, bacitracin, chlortetracycline, virginiamycin, monensin, and narasin.…”
mentioning
confidence: 99%
“…The microarray used in this study is based on earlier published work , which contains 312 oligonucleotides (70 bases in length) targeting 183 virulence or virulence-related genes and 30 of the most common antimicrobial resistance genes found in Gramnegative bacteria (Hamelin et al 2006). …”
Section: Dna Microarraymentioning
confidence: 99%
“…The tube was re-centrifuged as before and 150 mL of the supernatant containing DNA was removed and stored at (208C until used. Thawed lysate DNA was linearly amplified and labeled using the Bioprime † DNA Labeling System (Invitrogen Life Technologies, Burlington, ON) as described previously (Hamelin et al 2006). Briefly, 4 mL of RNase-treated supernatant were added to a final volume of 50 mL containing 20 mL of a random primer solution, 1 mL of persistent concentration DNA polymerase (Klenow fragment, 40 U mL…”
Section: Intestinal Tissuementioning
confidence: 99%